2013
DOI: 10.1039/c3cc45512b
|View full text |Cite
|
Sign up to set email alerts
|

A modular total synthesis of (±)-trigonoliimine C

Abstract: A convergent total synthesis of trigonoliimine C has been executed by employing three catalytic transformations in sequence. The key reactions that have been developed in this context include the [Au]-catalyzed addition of protected tryptamine to isatogens and the reduction of N-OH to NH with hydrazine monohydrate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(11 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…A solvent screen revealed that N-hydroxyindole formation occurred smoothly in ethereal solvents,b ut was attenuated in tert-butanol (entries 7-10). [11] To our surprise,t he identity of the counterion was critical to the reaction outcome:while no reaction was observed when lithium-or magnesium tertbutoxide was employed, 3-phenyl-3-hydroxy-2-oxindole 6a was obtained as the only product using potassium tertbutoxide irrespective of exposure to light (entries [11][12][13]. Thef ormation of 6a,w hose structure confirmed by X-ray crystallography, [12] involves not only oxygen transfer to the ortho-alkenyl substituent but also a[ 1,2]-phenyl shift.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A solvent screen revealed that N-hydroxyindole formation occurred smoothly in ethereal solvents,b ut was attenuated in tert-butanol (entries 7-10). [11] To our surprise,t he identity of the counterion was critical to the reaction outcome:while no reaction was observed when lithium-or magnesium tertbutoxide was employed, 3-phenyl-3-hydroxy-2-oxindole 6a was obtained as the only product using potassium tertbutoxide irrespective of exposure to light (entries [11][12][13]. Thef ormation of 6a,w hose structure confirmed by X-ray crystallography, [12] involves not only oxygen transfer to the ortho-alkenyl substituent but also a[ 1,2]-phenyl shift.…”
Section: Resultsmentioning
confidence: 99%
“…Thef ormation of 6a,w hose structure confirmed by X-ray crystallography, [12] involves not only oxygen transfer to the ortho-alkenyl substituent but also a[ 1,2]-phenyl shift. While oxygen transfer from nitroarenes to pendant acetylenes has been reported to afford N-heterocycles, [13] this oxidationmigration tandem reaction of ortho-alkenyl substituents is unprecedented.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…collected off Iheya Island, Okinawa . The iheyamines possess an intriguing azepinobisindole framework also present in the recently isolated natural product (−)-trigonoliimine C ( 3 ) (Figure ). Despite being isolated in 1999, Bremner’s attempted biomimetic synthesis of an iheyamine A model system remains the only report detailing synthetic efforts toward these alkaloids .…”
mentioning
confidence: 97%
“…Indolin-3-one with a quaternary stereocenter at the 2-position is frequently found as the privileged structure of numerous biologically active natural products and synthetic compounds (Figure ). Besides, C2-quaternary indolin-3-ones were usually used as important intermediates for natural product synthesis . Thus, the development of asymmetric synthetic approaches to access such valuable molecules has always been of interest among the scientific community .…”
mentioning
confidence: 99%